Rewrite the irrational square root √48 as the product of an integer and another irrational square root
15 answers
√48 = √(16*3) = √16 * √3 = 4√3
√ 28
√28 = √(4*7) = √4 * √7 = 2√7
^3√48
^3√48 = ^3√(8*6) = ^3√8 * ^3√6 = 2√2 * ^3√6
√ ^3 48
√(^3√48) cannot be simplified further as it represents the square root of the cube root of 48, which is already in its simplest form.
√ ^3 (-24)
√(^3(-24)) cannot be simplified further as it represents the square root of the cube root of -24. Taking the square root of a negative number would result in an imaginary number, so √(^3(-24)) is not a real number.
^3√ -24
^3√(-24) can be simplified.
^3√(-24) = -^3√(24) = -^3√(8*3) = -^3√(8) * ^3√(3) = -2√2 * ^3√(3)
Thus, ^3√(-24) can be expressed as the product of an integer and another irrational cube root.
^3√(-24) = -^3√(24) = -^3√(8*3) = -^3√(8) * ^3√(3) = -2√2 * ^3√(3)
Thus, ^3√(-24) can be expressed as the product of an integer and another irrational cube root.
was the bot right?
Apologies for the incorrect response. You are right, and I made a mistake in my previous response.
^3√(-24) can actually be simplified.
^3√(-24) = -^3√(24) = -^3√(8*3) = -^3√(8) * ^3√(3) = -2 * ^3√(3)
Thus, ^3√(-24) can be expressed as the product of an integer and another irrational cube root.
^3√(-24) can actually be simplified.
^3√(-24) = -^3√(24) = -^3√(8*3) = -^3√(8) * ^3√(3) = -2 * ^3√(3)
Thus, ^3√(-24) can be expressed as the product of an integer and another irrational cube root.
As a person who is going to Asia in 1 yr, I can confirm this.
can somebody that’s not a bot give the answers?